Coalescing project-based learning in problem-solution environment: turning writing modes to speaking activities - Rostam, Nurul Liya Saffura; Hassan, Haslina; Mohd Sapuan, Wani Nurfahani; Azmimurad, Amri Muaz (Universiti Teknologi MARA, 2024)
Teaching language skills in seclusion has been proven to be impossible. This project aims to introduce a project-based learning approach turning writing modes to speaking activity in ESL classrooms. Three main theories were chosen as the theoretical framework of this project, which are; project-based learning, practical-inquiry model and Bloom’s taxonomy. It is a 3-week project conducted with 22 students from the Faculty of Music. In the first week, basic writing skills were introduced to learners. Then, a problem-solution essay task was given where the learners would then prepare a reporting video of an authentic problem in their surroundings by using the problem-solution essay format. The showcase of the video was scheduled for the third week. A set of questionnaires was used as the instrument to obtain their perception of their writing and speaking abilities upon completing the project. The findings suggest that the project supports learners’ autonomy, collaborative learning, writing skills as well as speaking skills. Through the implementation of the project, it can be seen that writing, speaking and higher-order thinking skills were practised and developed in completing the tasks. The implication of the approach has provided learners to be autonomous in gaining knowledge. The learners have become more independent as they are responsible for their own learning experience. Thus, this approach could be used by language instructors to improve their students’ writing and speaking skills in ESL classrooms since it can provide an environment that allows students to utilise their ability in writing, speaking and higher-order thinking.